SEG Technical Program Expanded Abstracts 2017 2017
DOI: 10.1190/segam2017-17700260.1
|View full text |Cite
|
Sign up to set email alerts
|

Full-bandwidth adaptive waveform inversion at the reservoir

Abstract: Adaptive waveform inversion (AWI) is one of a new breed of full-waveform inversion (FWI) algorithms that seek to mitigate the effects of cycle skipping (Warner & Guasch, 2016). The phenomenon of cycle skipping is inherent to the classical formulation of FWI, owing to the manner in which it tries to minimize the difference between oscillatory signals. AWI avoids this by instead seeking to drive the ratio of the Fourier transform of the same signals to unity. One of the strategies most widely employed by FWI pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Facing challenging field data applications with alternative misfit functions is not widely documented in the literature. One of the only other alternative misfit functions that has been applied successfully to field data is adaptive waveform inversion (AWI) (Warner and Guasch, 2015;Ravaut et al, 2017;Debens et al, 2017;Roth et al, 2018;Guasch et al, 2019;Warner et al, 2019) or Kantorovich-Rubinstein optimal transport (KROT) (Poncet et al, 2018;Messud and Sedova, 2019;Sedova et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Facing challenging field data applications with alternative misfit functions is not widely documented in the literature. One of the only other alternative misfit functions that has been applied successfully to field data is adaptive waveform inversion (AWI) (Warner and Guasch, 2015;Ravaut et al, 2017;Debens et al, 2017;Roth et al, 2018;Guasch et al, 2019;Warner et al, 2019) or Kantorovich-Rubinstein optimal transport (KROT) (Poncet et al, 2018;Messud and Sedova, 2019;Sedova et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We point out that other meta-heuristic methods could have been chosen as for example genetic algorithms (GA) (Sen and Stoffa 2013). However, it was reported higher efficiency (Debens 2015) and suitability for continuous optimization (Kachitvichyanukul 2012) of QPSO over GA. QPSO belongs to a class of meta-heuristic optimization algorithms known as particle-swarm optim ization (Kennedy and Eberhart 1995). The latter emulates the dynamics of a swarm of particles ruled by the laws of classical mechanics.…”
Section: Quantum Particle Swarm Optimizationmentioning
confidence: 99%
“…As a result, the application of the global comparison methods, like the matching-filter and the optimal-transport methods, require some preprocessing and conditioning. For example, Huang et al (2017) reported that the matching-filter approach deals mainly with the diving waves and surfers from strong multiples (Debens et al, 2017).…”
Section: Introductionmentioning
confidence: 99%